Penerapan Sistem Kerjasama bagi Hasil Kebun Kelapa antara Pemilik Lahan dan Pekerja dalam Perspektif Ekonomi Islam di Desa Tanjung Solok Kabupaten Tanjung Jabung Timur Provinsi Jambi - Melta Vatmala Sari; Nurida Isnaeni; Yusuf Zaini Aprizal (Journal of Innovative and Creativity, 2025)
This study is about "Implementation of the Coconut Plantation Profit Sharing Cooperation System between landowners and workers in the Islamic Economic Perspective in Tanjung Solok Village, Tanjung Jabung Timur Regency, Jambi Province". This study aims to determine the implementation of the coconut plantation profit sharing cooperation system between landowners and workers in the Islamic Economic perspective in Tanjung Solok Village, Tanjung Jabung Timur Regency, Jambi Province. This thesis uses a qualitative approach with observation, interview and documentation data collection techniques, data analysis techniques are carried out with data reduction. The results of this study indicate that the coconut plantation profit sharing system in Tanjung Solok Village is implemented based on an oral agreement born from family deliberations and local customs. Cultivators bear all labor and maintenance costs, while the proceeds from the sale of coconuts are divided equally between landowners and cultivators. This agreement is not limited by time and can be continued by heirs if one party dies, although in practice there has been fraud from the cultivators. This cooperation has advantages such as opening up employment opportunities, sharing the risk of crop failure, and increasing plantation productivity. The socio-economic relationship between the parties is also closely connected. However, weaknesses remain, such as the potential for unclear agreements, the risk of deviation, lack of supervision, and uncertainty in the distribution of results because it is only based on verbal agreements. Therefore, a written agreement and increased legal awareness are needed so that this cooperation runs better. The profit sharing system for coconut plantations in Tanjung Solok Village is not yet fully in accordance with Islamic law. Several provisions such as the time limit, type, and nature of the musaqah contract are often not clearly stated, which causes disputes in the distribution of results and does not comply with the requirements for the validity of the contract according to Islamic law.